2018
DOI: 10.1097/mlr.0000000000000962
|View full text |Cite
|
Sign up to set email alerts
|

Ethnoracial Disparities in Medicare Annual Wellness Visit Utilization

Abstract: Utilization of the AWV has increased modestly since its introduction, but remains low. Utilization varies by ethnoracial group, with disparities largely explained by differences in income and education. Further efforts are needed to evaluate AWV utilization and effectiveness, especially among low socioeconomic status ethnoracial minorities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 12 publications
1
31
1
1
Order By: Relevance
“…Our study only had 6.3% Hispanics, whereas Hispanics represented 10.7% of the population in the previous study. 20 Hispanic particpants in the present study may be a more selected group and, thus, possibly healthier than the general Hispanic population in the US, because they represent a smaller proportion of the final study population compared to other studies. This may be explained by the strict selection criteria ( Figure A1), which may have influenced the inclusion of this race/ethnic group more than non-Hispanic white and black participants.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…Our study only had 6.3% Hispanics, whereas Hispanics represented 10.7% of the population in the previous study. 20 Hispanic particpants in the present study may be a more selected group and, thus, possibly healthier than the general Hispanic population in the US, because they represent a smaller proportion of the final study population compared to other studies. This may be explained by the strict selection criteria ( Figure A1), which may have influenced the inclusion of this race/ethnic group more than non-Hispanic white and black participants.…”
Section: Discussionmentioning
confidence: 76%
“…This is indirectly supported in a number of other studies that identified residence in more affluent areas and non-rural metropolitan areas to have higher AWV utilization. 11,18,20,21 Hispanic ethnicity and female sex were significantly associated with greater AWV utilization in the multivariable logistic regression analysis. Previous studies of sex are inconsistent.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations